1995
DOI: 10.1172/jci118066
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy enhances and estrogen replacement inhibits the activity of bone marrow factors that stimulate prostaglandin production in cultured mouse calvariae.

Abstract: To examine PG production in estrogen deficiency, we studied effects on cultured neonatal mouse calvariae of bone marrow supernatants (MSup) from sham-operated (SHAM), ovariectomized (OVX), or 1713-estradiol (OVX+E) -treated mice. MSups were obtained 3 wk after OVX when bone density had decreased significantly. 10-60% MSup increased medium PGE2 and levels of mRNA for inducible and constitutive prostaglandin G/H synthase (PGHS-2 and PGHS-1) and cytosolic phospholipase A2 in calvarial cultures. OVX MSups had twof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 59 publications
3
57
1
Order By: Relevance
“…E2 modulates OC apoptosis and OC activity both directly (37,38) and indirectly via regulation of growth factors and prostaglandins (39,40). Conversely, inhibition of OC formation in vivo results, in part, from the ability of E2 to block the production of the pro-osteoclastogenic cytokines IL-1, IL-6, and TNF (9 -13).…”
Section: Discussionmentioning
confidence: 99%
“…E2 modulates OC apoptosis and OC activity both directly (37,38) and indirectly via regulation of growth factors and prostaglandins (39,40). Conversely, inhibition of OC formation in vivo results, in part, from the ability of E2 to block the production of the pro-osteoclastogenic cytokines IL-1, IL-6, and TNF (9 -13).…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal women lose bone due to a decrease in ovarian estrogen and an increase in bone resorption. Previous studies have shown that inflammatory cytokines such as IL-1 and PGE 2 may be involved in the mechanism of bone loss due to estrogen deficiency (7,8). In the present study, we examined the effects of nobiletin on bone resorption in vitro and on bone mass in ovariectomized (OVX) mice.…”
mentioning
confidence: 94%
“…Nobiletin (5,6,7,8,3′,4′-hexamethoxy flavone), a citrus polymethoxy flavonoid, is abundantly present in Citrus depressa and has several biological activities. Previous studies have shown that nobiletin exhibits anti-proliferative and apoptotic effects on various cancer cells (3) and inhibits inflammation pathways (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ovariectomized (oVX) animals are widely used as a model of osteoporosis due to estrogen deficiency. oVX mice exhibit severe bone loss in the femur, and inflammatory cytokines such as IL-1, IL-6, and PGE 2 may be involved in the mechanism of bone loss due to estrogen deficiency [7][8][9]14]. These cytokines are also involved in the inflammatory pathogenesis of periodontitis [11].…”
mentioning
confidence: 99%